THE IMPLICATION OF PRE-SERVICE TEACHERS BELIEF ABOUT GRAMMAR TEACHING AND LEARNING FOR ENGLISH LANGUAGE POLICY IN INDONESIA - Cecilia Titiek Murniati; Angelika Riyandari (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
Recent studies have suggested that teachers beliefs have a significant influence on actual classroom practice and, consequently, on students achievements. However, little research has been done to investigate the influence of Indonesian language policy and teachers beliefs. The study reported seeks to examine the influence of English language policy on pre-service teacher's beliefs about the teaching of English language grammar in Indonesian schools. The research participants were pre-service teachers who have taken the subjects of Structure, Teaching Methods, and Micro-teaching in three public and private universities in Central Java and Yogyakarta Special District. Due to time and scheduling limitations, the sampling method used in this study was convenient sampling. Documentation, survey schedules, interviews, focus group discussions were used to gather the data. The findings revealed that although the language policy in Indonesia has put English language teaching and learning within the framework of communicative competence since the enactment of the 2006 School-based Curriculum, the pre-service teachers still believed that traditional method of teaching grammar (explicit grammar instruction) was imperative to use. The pre-service teachers tended to exclude English language policy enacted by Indonesian government in their discussion about teachers beliefs. Instead, the pre-service teachers constructed their beliefs about English language grammar teaching and learning process on their prior experiences in learning and teaching grammar.